Translation Techniques Applied in Relay Translation of Javanese Prohibition Advice - Sujatmiko (Borneo Educational Journal (Borju), 2022)
This study aims at exploring the translation techniques (TTs) applied by translators either in the mediated text (MT) or in the target text (TT) and their impact on translation quality (TQ). Data were collected through Focus Group Discussion (FGD). The results showcase that translator applied TTs such as established equivalent, explicitation, modulation, implicitation, paraphrase, transposition, addition, discursive creation, compensation, reduction, pure borrowing, particularization, and variation either in MT or TT translations. TTs applied have contributed to TQ such as reduction and discursive creation in TT, they produced less accurate translation. Discursive creation also had an impact on inaccurate translation in TT and less accurate in MT. Pure borrowing had an impact on less acceptable and medium readable of MT translation. Addition technique produced an accurate message, but it can impact on less acceptable in MT. Meanwhile, variation technique produced less acceptable translation. TTs such as established equivalent, explicitation, modulation, implicitation, transposition, addition, paraphrase, particularization, and compensation, contributed to the accuracy, acceptability and readability translation. It can be concluded that TTs applied by translator determine the TQ either in MT or in TT. Translator should apply TTs to make a good translation.